ANALISIS LITERASI KEUANGAN MAHASISWA PADA JURUSAN EKONOMI SYARIAH DI RANGKASBITUNG - Maskur Maskur; Budiman Budiman (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2021)
ABSTRACTIn Indonesia, The practice of Islamic financial institutions was strengthened by the implementation of the banking law number 10 of 1998, and fatwa from Indonesian Council of Religious Scholars of bank rate prohibition. Islamic financial institutions must be accompanied by more comprehensive understanding of Islamic economics itself. In this case, the Islamic economic understanding not only be technical socialization, background and history but also moral and how they had to bring their selves in accordance with sharia (Ibnu Taimiyah). It must be work together between the government and scholars in guiding and encouraging the community in terms of life in accordance with Islamic law. Based on the background above, the researcher focused on what factors that affected students' understanding of finance. The objective in this research is describing the level of students’ financial literacy by gender, age, year in, GPA, place of residence, parental education level and income level of parents. This research conducted in Lebak with 86 respondents of economic syariah majoring, and using quantitative descriptive analysis method One Way Anova. It is used to compare the average (mean) more than two samples, hypotheses testing, to reject or accepted H0 based P-value if sig. <Α 0.05, H0 is rejected and if sig. > Α 0.05 then H0 is accepted. The lowest value was 4% and the highest is 60%.The lowest is the respondents were able answer only one question from 25 questions, and The highest are the respondents were able to answer 18 questions correctly (60%). It was found that the mean of respondents is 7.74% and standard deviation of financial literacy mean (average) is 3,071. It can be concluded that the answers of the respondents was varied. The level of students’ literacy rate is divided into three parts, the highest, medium, and the lowest literacy. Only one respondent get the highest level (4%), and  one respondent get the medium level (4%), and the last 84 respondents get the lowest level (92%). So, it can be concluded that the students’ understanding of financial literacy is low, it was under <60%.Keywords: Gender, Age, Year In, GPA, Housing, Education Parents, And Income Parents, Financial Literacy.